Three-Dimensional Tomography of Pulsar Magnetospheres - McSweeney, Samuel James (Curtin University, 2019)
Pulsars (rapidly spinning neutron stars) emit beams of intense radiation in the radio part of the electromagnetic spectrum. How these beams are generated remains one of the unsolved mysteries in astrophysics. By studying the pulse-to-pulse variations in their radiation using multiple telescopes simultaneously, we can piece together a three-dimensional map of the intense environment surrounding these compact objects. The quasi-stable structures we observe in their radiation contain important clues to how the emission is generated.